2014
DOI: 10.1016/j.ccep.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Complications Related to Atrial Fibrillation Ablation and Strategies for Periprocedural Stroke Prevention

Abstract: Transcatheter treatment of atrial fibrillation (AF) is a complex intervention performed in patients who are at inherently increased risk of a thromboembolic complication, including stroke. It is therefore not surprising that cerebrovascular accidents have been among the most feared complications since the inception of AF ablation. While improvements have been made to limit the incidence of thromboembolic events during catheter ablation of AF, the optimal strategy to minimize such complications has yet to be de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Pulmonary vein isolation (PVI) is an established therapy for the management of atrial fibrillation (AF) with a low risk of a major complication, including thromboembolism [1][2][3]. Available data indicate that the risk of a clinical or a silent thromboembolic event is related to the periprocedural anticoagulation routine and the ablation technology used [4][5][6][7]. e interaction between coagulation activation and the different maneuvers and techniques used during an AF ablation procedure is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary vein isolation (PVI) is an established therapy for the management of atrial fibrillation (AF) with a low risk of a major complication, including thromboembolism [1][2][3]. Available data indicate that the risk of a clinical or a silent thromboembolic event is related to the periprocedural anticoagulation routine and the ablation technology used [4][5][6][7]. e interaction between coagulation activation and the different maneuvers and techniques used during an AF ablation procedure is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…The concern that these lesions might be related to cognitive decline is supported by limited data [22,23]. It has also been suggested that these lesions might be viewed as surrogates for the clinical stroke risk and are useful for an assessment of the risk involved with different ablation techniques and procedural changes [24]. The present data does suggest that TCD detection during LA ablation might improve our understanding of the micro-embolization process during these procedures.…”
Section: Discussionmentioning
confidence: 68%
“…The risk of a potentially life-threatening bleeding complication inherent to transseptal catheterization, catheter manipulation, and the delivery of ablative energy in the thin-wall LA argue against uninterrupted administration of any OAC in the absence of a specific antidote capable of restoring hemostasis in case of a bleeding complication. Despite these concerns, observational and randomized clinical trials have demonstrated the safety or even superiority of uninterrupted administration of vitamin K antagonists (VKA) [9][10][11]. Recently, different Non-Vitamin-K Oral Anticoagulants (NOACs) have also been studied in this clinical scenario.…”
Section: Introductionmentioning
confidence: 99%